2020
DOI: 10.1097/ico.0000000000002333
|View full text |Cite
|
Sign up to set email alerts
|

Performance of New Hypothermic Corneal Storage Media With an Antimycotic Tablet in Comparison to Traditional Hypothermic Media During Simulated Eye Bank Processing

Abstract: Purpose: To compare the performance of Kerasave (AL.CHI.MI.A. S.R.L., Ponte San Nicolò, Italy) containing 2.5 μg/mL of amphotericin B and Optisol-GS (Bausch & Lomb, Bridgewater, NJ) cold corneal storage media on donor corneas during routine eye bank procedures. Methods: Forty-four paired donor corneas were preserved after swab sample collection and povidone-iodine decontamination. Right and left corneas were immersed in Kerasave and Optisol-GS, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…23 24 45 Surprisingly, a very low log 10 decrease of 0.18 was observed for B. subtilis after 14 days in Kerasave, indicating a bacteriostatic rather than bactericidal effect for this strain under the tested conditions. Data in the literature reported B. subtilis to be sensitive to gentamicin (4.0 mg/L; 0.125 µg/mL) and resistant to streptomycin [45][46][47] ; the gentamicin content of Kerasave, which is significantly higher than that reported in the literature, led us to expect higher killing efficacy of B. subtilis spizizenii by Kerasave. The low killing efficacy was confirmed when we repeated the time-kill assay at 4°C and 31°C after 3 days of incubation to evaluate whether the incubation temperature could influence the killing efficacy of Kerasave (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…23 24 45 Surprisingly, a very low log 10 decrease of 0.18 was observed for B. subtilis after 14 days in Kerasave, indicating a bacteriostatic rather than bactericidal effect for this strain under the tested conditions. Data in the literature reported B. subtilis to be sensitive to gentamicin (4.0 mg/L; 0.125 µg/mL) and resistant to streptomycin [45][46][47] ; the gentamicin content of Kerasave, which is significantly higher than that reported in the literature, led us to expect higher killing efficacy of B. subtilis spizizenii by Kerasave. The low killing efficacy was confirmed when we repeated the time-kill assay at 4°C and 31°C after 3 days of incubation to evaluate whether the incubation temperature could influence the killing efficacy of Kerasave (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…An overview of the comparison between various storage solutions and the modifications for improving tissue viability and antimicrobial efficacy are provided in Tables 2 and 3. 14,[44][45][46][47][48][49][50][51][52][53][54]…”
Section: Organ Culture Methodsmentioning
confidence: 99%
“…Much attention has focused on interface fungal keratitis after EK, which is mostly due to Candida species, and thus amphotericin B has been investigated extensively as an antifungal additive to storage solution. 14,49,50,52,64,74,75 Although many studies have demonstrated its efficacy against Candida, amphotericin B's safety to the corneal endothelial cells still needs further research, especially at the higher concentrations that have been found to be most effective for eradication of Candida. Furthermore, although EK is the more commonly performed keratoplasty procedure compared with PK in the United States and some other areas, globally, PK is the most performed procedure.…”
Section: Antimicrobial Coveragementioning
confidence: 99%
“…The main characteristics of the included studies, such as storage conditions, time and temperature ranges, the comparative distinct exposition media, and the assessment methods are shown in Table 4. Of the 14 included studies, 13 evaluated the effect of preservation in human corneas [5,12,[22][23][24][25][26][27][28][29][30][31][32]; 1 study was performed with rabbit cornea for a preclinical evaluation of new intermediate storage media with simple formulations [8].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Optisol-GS was compared with seven distinct commercial media: Chen medium [31], Cornea Cold medium [13], Cornisol [22], Dexsol [25], Eusol-C [27], Kerasave [30,32], and Sinasol [26]. Optisol-GS was also compared with other compositions, such as a coconut water-based solution [23], Optisol-GS supplemented with antibiotics [24,28,29,33], and a minimum essential medium (MEM) with supplements [33].…”
Section: Study Characteristicsmentioning
confidence: 99%